Study on Levitation Control Method Based on Multi-dimensional Taylor Network Optimal Control - Lin ZHU; Yi JIANG; Laisheng TONG; Wenyue ZHANG (机车电传动)
Aiming at the problem that the levitation system of the maglev train has strong nonlinearity and the control effect of the commonly used linear control law is not ideal, the nonlinear control law of the levitation system based on multi-dimensional Taylor network (MTN) optimal control was proposed. The simulation results showed that the control law based on MTN optimal control had better anti-interference performance for gap and load than PID control law.